Marketing digital en el Almacén Don Pato de la ciudad de Babahoyo - Bustamante Santillán, Shirley Graciela (2022)
The market is no longer the same as in previous years, likewise customers have changed their expectations and it is the internet that has revolutionized consumption, since most organizations include it as a work tool, their best ally. The many advantages of staying online, but even more so is global connectivity and computer networks that work hand in hand with what is now referred to as Digital Marketing, an instrument that manages to satisfy and adapt resources to needs. humans through the network. Social Networks reveal a lot of the work that must be maintained in order not to speculate on the recognized Fake News, to maintain customer loyalty that leads organizations to success, maintaining competitive visibility.